Modelling of reinforced concrete beam by using plasticity approach [electronic resource] - Nur Fatiha Nadia Mansor, 1992-; Fakulti Kejuruteraan Awam (2016)
Thesis (Sarjana Kejuruteraan (Awam - Struktur)) - Universiti Teknologi Malaysia, 2016